Democratic drift majoritarian modification and democratic anomie in the United Kingdom - Flinders, Matthew V. (Oxford : Oxford University Press, 2010)
This text examines the evolution of democracy in the UK since the election of New Labour in 1997. Flinders also explores the trajectory of democracy from 1945 onwards and examines the degree to which recent developments in the UK fit within global democratic trends.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Democracy -- Great Britain -- History -- 20th century; Democracy -- Great Britain -- History -- 21st century; Labour Party (Great Britain); Great Britain -- Politics and government -- 1945-